Standard of care and outcomes of primary laparotomy versus laparotomy in patients with prior open abdominal surgery (ReLap Study; DRKS00013001) - Tran, Dinh Thien-An; Klotz, Rosa; Harnoß, Julian-Camill; Heger, Patrick; Ritter, Alina; Dörr-Harim, Colette; Knebel, Phillip; Schneider, Martin; Büchler, Markus W.; Diener, Markus K.; Probst, Pascal (Journal of gastrointestinal surgery, 2021)
Patients undergoing relaparotomy are generally underrepresented in trials, despite how common the procedure is in clinical practice. The aim of this trial was to determine standard of care and gain evidence of intra- and postoperative outcomes for patients undergoing relaparotomy compared to primary laparotomy.